2016
DOI: 10.2516/ogst/2016013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pH on Oil-Water Interfacial Tension and Mass Transfer for Asphaltenes Model Oils. Comparison with Crude Oil Behavior

Abstract: -Asphaltenes are shown to be amphoteric, containing acidic and basic species that can ionize at low and high pH respectively when they come in contact with water. We have used a mass transfer model in order to determine the partition coefficients of asphaltenes between oil and water. We have compared the influence of type of asphaltenes on interfacial tension and on mass transfer between oil and water and analysed the influence of an added surfactant. We have also compared the behavior of asphaltenes dissolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…It should be mentioned that the initial value of pH (reported in this work) might not be the most important variable, but the final pH of the system and the residual naphthenic acid in the oil after contacting with the alkaline solution are Hutin et al () showed that, in acid crude oils and asphaltene solutions, the initial pH of the aqueous phase needs to be greater than 10.5 in order to have a final pH in the emulsion of greater than 8. This is an important finding because it shows that one needs to clarify under what condition is the pH reported (before or after contacting the oil) and because the observation in asphaltene solutions suggests that there is an acidic fraction of asphaltenes that could be interfacially active at high pH values.…”
Section: Resultsmentioning
confidence: 71%
“…It should be mentioned that the initial value of pH (reported in this work) might not be the most important variable, but the final pH of the system and the residual naphthenic acid in the oil after contacting with the alkaline solution are Hutin et al () showed that, in acid crude oils and asphaltene solutions, the initial pH of the aqueous phase needs to be greater than 10.5 in order to have a final pH in the emulsion of greater than 8. This is an important finding because it shows that one needs to clarify under what condition is the pH reported (before or after contacting the oil) and because the observation in asphaltene solutions suggests that there is an acidic fraction of asphaltenes that could be interfacially active at high pH values.…”
Section: Resultsmentioning
confidence: 71%
“…8. The asphaltene/resin ratio evaluates the asphaltene instability because resin stabilizes asphaltene in crude oil [57][58][59][60][61] . A high asphaltene/resin ratio typically indicates asphaltene being unstable.…”
Section: Correlation Between Wettability Alteration and The Microdispmentioning
confidence: 99%
“…Once in contact with an aqueous phase, water-soluble hydrocarbons in the crude oil will partition into the water phase [22][23][24] , adsorb at the gas-water interfaces and influence the oil removal efficiency by gas flotation [25][26] . The characteristics of the produced water also depends on the properties, like pH [27][28] , ionic strength 29 and the presence of divalent ions 30 .…”
Section: Introductionmentioning
confidence: 99%